Digital Marketing Communication Strategy For Sesek Woven Fabrics On A Digital Platform With A Marketing Approach Mix's 8p Sade Village Sasak Tribe Lombok - Wulan, Rayung; Ariyani, Nafiah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The digital marketing communication strategy for Sesek woven fabric on a digital platform with a marketing approach based on the Mix's 8P marketing model in Sade Village, Sasak tribe, Lombok was designed as an effort to increase the digital marketing needed by village girls. This research aims to identify and analyze the effectiveness of digital marketing strategies in promoting Sesek woven fabric, by integrating digital marketing platforms by adopting Marketing Mix's (8P) which involves product, price, place, promotion, people, process, physical evidence and customer participation. The research method was descriptive qualitative and in-depth interviews with Sade village girls craftsmen and consumers of Sade village woven cloth. The research results were obtained using Mix's 8P marketing model, the application of digital marketing strategies increases the visibility and sustainability of the marketing of Sesek woven fabric, which is unique and has cultural value, in the digital era. Practical implications and recommendations for further development in the context of digital marketing of local woven fabric products for village girls and Sesek woven fabric craftsmen